Prospective comparison of 68Ga-PSMA PET/CT, 18F-sodium fluoride PET/CT and diffusion weighted-MRI at for the detection of bone metastases in biochemically recurrent prostate cancer - Zacho, Helle Damgaard; Nielsen, Julie B.; Afshar-Oromieh, Ali; Haberkorn, Uwe; DeSouza, Nandita M.; De Paepe, Katja; Dettmann, Katja; Langkilde, Niels C.; Haarmark, Christian; Fisker, Rune V.; Arp, Dennis T.; Carl, Jesper; et al. (European journal of nuclear medicine and molecular imaging, 2018)
To prospectively compare diagnostic accuracies for detection of bone metastases by 68Ga-PSMA PET/CT, 18F-NaF PET/CT and diffusion-weighted MRI (DW600-MRI) in prostate cancer (PCa) patients with biochemical recurrence (BCR).
Gesehen am 10.03.2020
Im Titel sind die Zahlen 68 und 18 hochgestellt